BENTUK DAMPAK INDUSTRI TAMBANG PADA TRANSFORMASI ASET SUMBERDAYA ALAM MASYARAKAT DI SEKITAR DESA MOROSI KECAMATAN MOROSI KABUPATEN KONAWE - Nurul Fitriani; Anas Nikoyan; Iskandar Iskandar (Universitas Halu Oleo, 2023)
PT. Virtue Dragon Nickel Industry (VDNI) is the largest nickel mining company located in Morosi Village, Morosi District, Konawe Regency, operating from 2015 to the end of 2018. Before there was a mine in Morosi Village, most people depended on the agricultural sector, but not able to meet their daily needs. This study aims to find out: the impact of the VDNI industry on the transformation of natural resources assets of farming communities, the transformation of natural resources assets into economic assets of farming communities around the VDNI industry, and the economic transformation of farming community assets with the existence of the VDNI industry. This research was conducted in Morosi Village, Morosi District, Konawe Regency which was carried out in January 2022 with a total of 20 informants. Data analysis in this study used qualitative methods. The results of the study show that the impact of the VDNI industry on the transformation of natural resource assets is (a) migration. In this case, the socio-economic conditions in the area of origin that make it impossible to meet one's needs cause that person to want to go to another area that can meet those needs. This also happened in Morosi Village, with the PT VDNI industry attracting many migrants from various regions who aim to meet economic needs with various kinds of jobs such as being workers in the PT VDNI Industry and opening businesses (restaurants, immigrants buying local community land then leasing back the land to newcomers who open a cloning business and selling vegetables), Laborers of a boarding house building in Morosi Village. (b) Change of profession This also happened in Morosi Village, after the entry of the industry PT VDNI demanded that the community change their profession from agriculture to non-agriculture by freeing up part of the agricultural land to set up industries which of course had an impact on changing livelihoods. (c) Environmental pollution, observing the phenomenon of environmental impacts in the area around mining, in fact creates both positive and negative environmental impacts for the community. The inclusion of nickel mining in an area gives people hope for job creation, improvement of health service facilities such as health centers, as well as assistance for environmental sanitation facilities for villages and educational assistance. Nickel mining activities are non-renewable natural resource exploitation activities, in mining activities can have an impact on ecosystem damage. A damaged ecosystem is defined as an ecosystem that can no longer carry out its functions optimally, such as soil protection.